Some remarks on the polyvalence of the term association from a neurocognitive perspective of the lexicon - Carmen Varo Varo (Revista de Lingüística y Lenguas Aplicadas)
The concepts of association and associative are present in lexical studies since the dawn of modern linguistics. They have been the subject of multiple conceptual interpretations but not without problems. Both conceptions of associative relationship as a connection between the two psychological faces of the linguistic sign and as in absentia relationships coexist, especially in Linguistics dictionaries, with the interpretation (almost opposite) as connotation or, in other words, as a sense relationship which lies outside of word meaning. In contrast, current advances in the neurocognitive research of the lexicon, which have contributed to the reconstruction of the semantic system from a cerebral perspective, lead us necessarily to a new interpretation of these notions that is transferred from the word level to its formal and semantic traits.